Performance of a Semiquantitative Multiplex Bacterial and Viral PCR Panel Compared With Standard Microbiological Laboratory Results: 396 Patients Studied With the BioFire Pneumonia Panel. (29th November 2020) - Rand, Kenneth H; Beal, Stacy G; Cherabuddi, Kartikeya; Couturier, Brianne; Lingenfelter, Beth; Rindlisbacher, Cory; Jones, Jay; Houck, Herbert J; Lessard, Kylie J; Tremblay, Elizabeth E
Abstract: Background: Microbiologic results are critical to optimal management of patients with lower respiratory tract infection, but standard methods may take several days. The multiplex polymerase chain reaction BioFire Pneumonia (PN) panel detects 15 common bacterial species semiquantitatively as copy number/mL, 8 viral species, and 7 resistance genes in about an hour within the clinical laboratory. Methods: We tested 396 unique endotracheal or bronchoalveolar lavage specimens with the BioFire Pneumonia panel and compared the bacterial detections to conventional gram stain and culture results. Results: Of the 396 patients, 138 grew at least 1 bacterium that had a target on the PN panel, and 136/138 (98.6%) were detected by the panel. A total of 177 isolates were recovered in culture and the PN panel detected 174/177 (98.3%). A further 20% of patients had additional targets detected that were not found on standard culture (specificity 69%, positive predictive value 63%, and negative predictive value 98.9%). Copy number was strongly related to standard semiquantitative growth on plates reported by the laboratory (eg, 1+, 2+, 3+ growths) and was significantly higher in those specimens that grew a potential pathogen. Both higher copy number and bacterial detections found by the PN panel, but not found in culture, were strongly positively related to the level of white blood cells reported in the initial gram stain. Conclusions: Higher copy number and bacterial detections by the PN panel are related to the host respiratory tract inflammatory response. If laboratories can achieve a rapid turnaround time, the PN panel should have a significant impact both on patient management and on antibiotic stewardship.